Deficiency of the NHE1 Gene Prevents Hypoxia-induced Pulmonary Hypertension and Vascular Remodeling - Yu, Lunyin (American Thoracic Society, 2008)
Rationale: Our previous studies found that Na(+)/H(+) exchanger (NHE) activity played an essential role in pulmonary artery smooth muscle cell (PASMC) proliferation and in the development of hypoxia-induced pulmonary hypertension and vascular remodeling. Other investigators recently observed increased expression of the NHE isoform 1 (NHE1) gene in rodents with pulmonary hypertension induced by hypoxia. However, a causal role for the NHE1 gene in pulmonary hypertension has not been determined. Objectives: To determine the causal role of the NHE1 gene in pulmonary hypertension and vascular remodeling. Methods: We used NHE1-null mice to define the role of the NHE1 gene in the development of pulmonary hypertension and remodeling induced by hypoxia and to delineate the NHE1 regulatory pathway. Measurements and Main Results: After 2 weeks of exposure to hypoxia, in contrast to wild-type hypoxic littermates, there was no significant increase in right ventricular systolic pressure, in the ratio of right ventricular to left ventricular plus septal weight [RV/(LV + S)], or in medial wall thickness of the pulmonary arterioles in homozygous mice (NHE1(−/−)). There was a significant decrease in Rho kinase (ROCK1 and ROCK2) expression, accompanied by an increase in p27 expression in NHE1(−/−) mice. Conclusions: Our study demonstrated that deficiency of the NHE1 gene prevented the development of hypoxia-induced pulmonary hypertension and vascular remodeling in mice and revealed a novel regulatory pathway associated with NHE1 signaling.